The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Chapitre 2. Le mouvement anti-esclavagiste et la naissance des droits des femmes. - Davis, Angela Yvonne (Femmes, race et classe, 1983)
Etude socio-historique de la condition des femmes noires aux Etats-Unis; aspect particulier de l'esclavage des femmes noires; persistance des problèmes après l'abolition de l'esclavage.
Section: 341 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; corps; cours; discipline; droits des femmes*; esclavagisme; féminisme afroaméricain; féminismes noirs; histoire et politique; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; états-unis

Question de différence - Guillaumin, Colette (Questions Féministes, 1979)
La « différence » est une relation entre hommes et femmes qui assigne à l'un des groupes, celui des femmes, des obligations matérielles envers l'autre groupe ; imposées par des signes dans le corps (motricité entravée, vête-ments, usage de l'espace et du temps) elles nous à intérioriser la soumission et la disponibilité. La différence n'est ni « naturelle » ni bonne en soi. Conséquence banale de ce qui nous est imposé socialement, elle est l'expression de la relation de pouvoir entre hommes et femmes, Revendiquer un « droit à la différence » est acte d'allégeance au « Réfèrent » . Et qui est le Réfèrent ?
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; approches et analyses; corps; cours; discipline; europe; france; féminisme matérialiste; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques